Natural History of Anal Papillomavirus Infection in HIV-Negative Men Who Have Sex With Men Based on a Markov Model: A 5-Year Prospective Cohort Study - Zhang, Zewen; Ling, Xi; Liu, Lirong; Xi, Miaomiao; Zhang, Guozhen; Dai, Jianghong (Frontiers in Public Health, 2022)
Objective To assess the incidence, clearance and duration of anal human papillomavirus (HPV) infection in HIV-negative men who have sex with men (MSM) and the influencing factors in a 5-year prospective cohort study. Methods From April 2016 to April 2021, HIV-negative MSM were recruited and followed every 6 months in Urumqi, Xinjiang, China. Questionnaires and anal swabs were collected at baseline and every 6 months. We detected 37 anal HPV genotypes using the HPV Geno Array Diagnostic Kit Test. Incidence and clearance rates of anal HPV infection and the influencing factors were estimated using a two-state Markov model. Results 585 MSM, with a median age of 37 years [interquartile range (IQR): 31–43 years], were followed for a median 2.8 years (IQR: 1.8–3.6 years). Incidence rates for any HPV and high-risk HPV (Hr-HPV) were 53.4 [95% confidence interval (CI): 49.1–58.0] and 39.0 (95% CI: 35.7–42.5)/1000 person-months. Median duration of infection was 9.67 (95% CI: 8.67–10.86) and 8.51 (95% CI: 7.57–9.50) months, respectively. Clearance rates for any HPV and Hr-HPV were 50.9 (95% CI: 46.7–55.3) and 62.1 (95% CI: 56.8–66.7)/1000 person-months, respectively. HPV6 and HPV16 had the highest incidence, lowest clearance rate and longest duration of infection. Receptive anal sex is a risk factor for any HPV [hazard ratio (HR)=1.66, 95% CI: 1.16–2.38] and Hr-HPV infection (HR=1.99, 95% CI:1.39–2.85). Recent anal sex without condom use was significantly associated with any HPV (HR=1.80, 95% CI: 1.10–2.94) and Hr-HPV infection (HR=2.60, 95% CI: 1.42–4.77). Age ≥35 years was significantly associated with low-risk-HPV infection only (HR=1.40, 95% CI: 1.02–1.93). Both inserted and receptive anal sex (HR=0.60, 95% CI: 0.40–0.89) and anal sex ≥2 times per week (HR=0.61, 95% CI: 0.43–0.87) were associated with reduced Hr-HPV clearance. Six of the nine-valent vaccine types (HPV6, 11, 16, 18, 52 and 58) occurred most frequently, which indicates the need for high vaccination coverage in MSM. Conclusions In this long-term cohort, high incidence and low clearance of any HPV, Hr-HPV and individual HPV infections emphasize the importance of MSM vaccination. Modifiable behavioral factors such as condoms and drug use should be incorporated into HPV prevention strategies.